The influence of motivation, commitment and workload on job satisfaction of regional officials with competency as intervening variable in Regional Financial Agency of Riau Islands Province - Ngaliman Ngaliman; Nike Astarina; I Wayan Catrayasa (Goodwood Publishing, 2024)
Purpose: This study analyzes the influence of motivation, organizational commitment, and workload on the job satisfaction of regional officials, with competence as an intervening variable at the Regional Financial and Asset Agency of Riau Islands Province. In 2023, delays occurred in 11,380 files (49.26%) from SPP to SP2D, indicating the urgency to improve employee satisfaction and performance. Research/methodology: Primary data were collected from 143 employees and analyzed using SEM-PLS. Motivation, commitment, and workload were examined as predictors of competence, while competence was tested as a mediator toward job satisfaction. Results: Motivation showed no significant direct effect on job satisfaction. However, motivation, organizational commitment, and workload significantly influenced competence, which in turn strongly mediated their impact on job satisfaction. The findings confirm that higher competence enhances employees’ satisfaction and performance, emphasizing the importance of competence development to minimize delays and strengthen service quality. Conclusions: Job satisfaction is not directly determined by motivation but is mediated by competence, organizational commitment, and workload. Competence development becomes a strategic factor in improving overall satisfaction and organizational performance. Limitations: The study was limited to one institution in Riau Islands Province, thus reducing generalizability. Comparative studies across multiple agencies and provinces are recommended. Contribution: This study enriches HRM literature by confirming the mediating role of competence in public sector organizations. Practically, it guides policymakers to improve satisfaction and performance through competency development, balanced workload distribution, and organizational commitment programs.